RANCANG BANGUN SISTEM TRAINER RADIO FM SEBAGAI PEMBELAJARAN MAHASISWA PADA LABORATORIUM ELEKTRONIKA DAN TELEKOMUNIKASI FAKULTAS TEKNIK UNIVERSITAS NEGERI GORONTALO - Arune, Abdul Hayan; Tansa, Salmawaty; Bonok, Zainudim (Universitas Bina Taruna Gorontalo, 2024)
Abstract: Design and Construction of an FM Radio Trainer System for Student Learning at the Electronics and Telecommunications Laboratory, Faculty of Engineering, Gorontalo State University. This research aims to build an FM Radio Trainer as student learning in the Basic Telecommunication Engineering course. The method used in this research is literature study and experimentation. The FM Radio Trainer design uses IC LA1260 as an FM Tuner and IF Amplifier, IC LA3361 as a Multiplexer and Demodulator, IC TDA 2004 as a Power Amplifier. The test results were carried out to measure the parameters VAntenna, VCC, IF, AFC (IC LA1260), MPX, Demodulator, VRight, VLeft (IC LA3361), VRight input Output, VLeft Input Output (IC TDA2004). The test results carried out on RRI Pro1 FM 101.8MHz Radio broadcast show that the results are in accordance with the tuning frequency. The gain of the output signal (A) occurs 5 times that of the input signal and the sound intensity level is 13.9 dB.